The Impact Assessment of the Errors in Determining the Mass and Zero Lift-Drag Coefficient on the Aircraft’s Performance Data - Klyagin Viktor Anatolievich; Laushin Dmitry Andreevich (Advances in Science, Technology and Engineering Systems Journal, 2020)
The adoption of technical decisions in the development of a new aircraft is carried out under the condition of insufficient information on the mass – dimensional and aerodynamic characteristics that will be achieved during the project. Insufficient information on the input parameters (weight and aerodynamic characteristics) leads to uncertainties in the values of the flying qualities and performances. When creating a new aircraft, the chief designer and specialists of the design bureaus establish certain reserves (limits) for mass and aerodynamic characteristics. The allocation of reserves for the characteristics of aircraft elements is carried out, as a rule, on the basis of experience gained from previous projects, and to a certain extent subjective. At the same time, it is not possible to quantify the risk of non-fulfillment of the tactical and technical task in terms of performance characteristics. Knowing the contribution of the uncertainties of the input parameters (for the values of which a margin is allocated) to the uncertainty of the final values of the flight characteristics will allow the person who makes the decision to reasonably establish reserves in the design of the aircraft and take a more reasonable risk. In this paper, the authors describe an approach that allows for a quantitative assessment of the impact assessment of the errors in determining the aircraft’s characteristics on the tactical and technical task in terms of the aircraft’s performance data. Using the example of the mass and zero lift-drag coefficient, analytical dependencies are derived that allow a quantitative assessment of the effect. To verify the obtained analytical dependencies, the calculation of weight coefficients was made for several aviation complexes of operational-tactical aviation. The analysis of the sensitivity of the aircraft’s performance data to the parameters under consideration is carried out.
Keywords: Uncertainties; Risks; Flying qualities and performances; Influence coefficients